Corporate legal structure and bank loan spread - Sikochi, Anywhere (Journal of Corporate Finance, 2020)
This study examines how a firm's corporate legal structure may affect its borrowing costs. Corporate legal structure refers to the legal fragmentation of a firm into multiple, separately incorporated entities. This fragmentation is bound to be a factor when lenders determine the pricing of debt and design of contract terms because they can enter into legally enforceable agreements only with specific legal entities. Using a sample of private loans to parent companies in the United States, I find that a more complex corporate legal structure is associated with higher loan spread. The findings are robust to several firm and loan characteristics and are incremental to the effects of other forms of organizational structure, namely business and geographic diversification. Subsequent evidence suggests that the effect of a corporate legal structure on borrowing costs is, at least partly, explained by recovery risk.